An Electronic Alert System Is Associated With a Significant Increase in Pharmacologic Venous Thromboembolism Prophylaxis Rates Among Hospitalized Inflammatory Bowel Disease Patients. Issue 5 (September 2017) - Mathers, Bradley; Williams, Emmanuelle; Bedi, Gurneet; Messaris, Evangelos; Tinsley, Andrew
Abstract : Background: Utilization of pharmacologic venous thromboembolism (VTE) prophylaxis in inflammatory bowel disease (IBD) patients seems to be suboptimal with reported rates as low as 50% in some studies. Implementation of an electronic alert system seems to be an effective tool for increasing VTE prophylaxis rates in medical inpatients. To date, no studies have assessed whether this approach is associated with improved rates of pharmacologic VTE prophylaxis specifically in IBD patients. Aims: To determine the efficacy of an electronic alert in improving VTE prophylaxis rates in hospitalized IBD patients. Methods: We conducted a retrospective cohort study of 576 hospitalized IBD patients. The medical record of each patient was then examined to determine whether pharmacologic VTE prophylaxis was both ordered and administered, the timing of pharmacologic VTE prophylaxis, and reasons for any missed doses. Results: The VTE pharmacologic prophylaxis rate was improved from 60% to 81.2% following the implementation of the electronic alert system ( p < .001). An increase in prophylaxis rates was seen in both medical (26.3% vs. 62.8%, p < .001) and surgical services (83.7% vs. 95.5%, p < .001). In patients who received pharmacologic VTE prophylaxis, 16% of all ordered doses were not administered and 57.3% of missed doses were the result of patient refusal. Hospitalization after implementation of the electronic alert system (odds ratio [OR] 4.71, 95% confidence interval [CI] 2.94–7.57) and admission to a surgical service (OR 14.3, 95% CI 8.62–24.39) were predictive of VTE pharmacologic prophylaxis orders. Conclusions: The introduction of an electronic alert system was associated with a significant increase in rates of pharmacologic VTE prophylaxis. However, orders were often delayed and doses not always administered. The most common reason that ordered doses were not given was patient refusal.